Ijtihad: Concept, requirements, derivatives, and issues from Imam Zakariya Al-Sunaiki´s perspective - Suad Al-Waely, Tar Abdallahi, Mohammad Issa Alhourani, (Opción, 2020)
This research paper focuses on the work of Imam Zakariya Assunaiki: Ghayat al-Wusul. In addition, the paper will also clarify the term and address the requirements of Ijtihad and its status in sharia via comparative qualitative research methods. As a result, ijtihad is a central concept in the discipline of Principles of Jurisprudence. In conclusion, Zakariya’s work was successful; it was a well-researched and thoroughly analyzed ad hoc study, presenting the concept in a way that both the general reader and researcher find useful.